Impact of COVID-19 on the change in work conditions and career choices in general Vietnamese population - Doan, Linh Phuong (2023)
Objectives: The onset of COVID-19 has resulted in both morbidity and mortality. It also has a consequential impact on the Vietnamese economy. Prior studies have examined the impact of COVID-19 on healthcare professionals’ career decisions. However, no study remains to have examined the work conditions and career choices in a general Vietnamese population. Our study aims to identify factors associated with the change in work conditions and career choices in general Vietnamese population. Methods: An online cross-sectional study between September 2021 through to November 2021 (during the Omicron COVID-19 pandemic). Snowball sampling method was utilized in recruiting the participants. The questionnaire used in this study included the following questions: (a) Socio-demographic information; (b) impact of COVID-19 on personal habits/daily expenses; (c) Current nature of work and impact of COVID-19 on work; (d) Impact of COVID-19 on career decisions. Data analysis was performed using STATA version 16. Descriptive analysis followed by Ordered logit regression was performed, to identify potential covariates. Results: Six hundred and fifty participants were recruited, of which only 645 completed the survey. The completion rate was 99.2%. This study demonstrated the impact that COVID-19 has on finances, as only 32% of those sampled reported that they were able to pay in full. 46.6% of the respondents have had a decrease in their overall household income. With regards to their employment and work characteristics, 41.0% reported a decrease in their work satisfaction and 39.0% reported having reduced motivation for work. Females were less likely to consider transiting from their current job to another field than male participants. Respondents who were married, had a higher level of commitment to their current job, and lower inclination to transition to another field. Respondents experiencing financial difficulties were more likely to consider a transition to another field/work. Conclusion: This is perhaps one of the first studies to have examined the impact of COVID-19 on work intentions regarding career choices and transitions in the general Vietnamese population. Future financial policies must take into consideration these factors.